Գիտական աստիճանաշնորհման համակարգի արդիանականացման իրավական հարցեր - Մխիթարյան, Ատոմ (Զանգակ հրատ.)
В статье представлено законадельство РА, регулирующее систему присвоения ученых степеней, процедуры, основные субъекты и их функции. Предлагется ряд принципиальных изменений для модернизации системы. The legislation for the regulations of the academic degree awarding system of RA, procedures, main subjects and its functions are presented in the article. A number of principal changes are suggested for the modernization of the system.
Keywords: Կրթության մենեջմենթ